Intra‐Annual Changes in Waterborne Nanophyetus salmincola. Issue 3 (19th June 2019) - Hershberger, P. K.; Powers, R. L.; Besijn, B. L.; Rankin, J.; Wilson, M.; Antipa, B.; Bjelland, J.; MacKenzie, A. H.; Gregg, J. L.; Purcell, M. K.
Abstract: An analysis of daily water samples collected from an index site on Big Soos Creek, Washington indicated intra‐annual differences in the concentrations of waterborne Nanophyetus salmincola . Waterborne concentrations, quantified as gene copies/L, peaked during the fall (October–November 2016), decreased to very low concentrations over the winter (January–March 2017), and then increased in the spring and throughout the summer. High waterborne concentrations of N. salmincola DNA (2 × 10 6 gene copies/L) corresponded with live N. salmincola cercariae (mean = 3 cercariae/L) that were detected in companion water samples. Spikes in waterborne N. salmincola concentrations in October and November typically coincided with increases in streamflow; this combination resulted in elevated infection pressures during high water events in the fall. The peak in waterborne N. salmincola concentrations corresponded with an accompanying peak in tissue parasite density (metacercariae/posterior kidney) in Coho Salmon Oncorhynchus kisutch that were reared in the untreated water.